Kritik Sosial Dalam Naskah Drama Dor Karya Putu Wijaya - Putri Aulia Rahmawati; Indrayuda (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This study aims to find out how social criticism is in the script of the drama DOR by Putu Wilayah. The object used in this study is a series of events in the script of the drama DOR by Putu Wijaya which contains social criticism. This manuscript was published by Balai Pustaka in 1985. This research is a qualitative research with a descriptive method. The data collection technique is to read and understand the script of the drama DOR by Putu Wijaya, mark the speeches of the characters and narrators in the script of the drama DOR by Putu Wijaya, then record the findings on the record sheet, and inventory the characters contained in the script of the drama DOR by Putu Wijaya in a table format. The data analysis technique is to classify data on social criticism contained in the script of the drama DOR by Putu Wijaya through the speech of the characters, the actions of the characters and the narrator's exposure, interpret the data on social criticism in the script of the drama DOR by Putu Wijaya and draw conclusions and report the results of data analysis. Based on the results of data analysis, it was found that the forms of social criticism in the DOR drama script by Putu Wijaya include, among others, (1) Social criticism of norm violations, (2) Social criticism of family disorganization, (3) Social criticism of crime handling, (4) Social criticism of poverty.